Quuer representations in cartoon network’s Steven Universe: Encoding gender subversive signs in children’s animation / Asyraf Syahir Mohd Najib - Asyraf Syahir , Mohd Najib (2019)
This research is conducted with the premise that Cartoon Network’s Steven Universe, utilizes its fantasy-themed narrative to enable the encoding of gender-subversive meanings in the connotative layers of the visual and verbal signs of the animation. The reality, as constructed in the animation, is hypothesized to be able to accomplish performative functions in subverting intelligible gender identities through its multi layered sign systems. Understanding that Steven Universe is an animation intended mainly for children, the author believes that the interplay of gender queer meanings in the cartoon, is a phenomenon worth paying attention to. Consequently, to analyse subversive visual and verbal signs in Steven Universe, the author proposes the Structural Multisemiotic Model for Connotative-Performativity. The model employs a synthesized framework between Semiotics and Gender Performativity. Findings have ultimately confirmed the initial hypothesis that Steven Universe encode gender subversive meanings into its visual and verbal signs through the signification of queer concepts.